2005
DOI: 10.1038/sj.ijo.0802982
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of long-term weight loss studies in obese adults: clinical significance and applicability to clinical practice

Abstract: BACKGROUND: Obesity is a common health problem that requires a long-term care approach. We systematically reviewed long-term (Z2 y) studies investigating dietary/lifestyle, pharmacologic, and surgical weight loss methods to assess (1) weight loss efficacy, defined by absolute weight loss and the proportion of subjects with Z5% weight loss, (2) effects of weight loss on cardiovascular risk factors, and (3) applicability of findings from studies to everyday clinical practice. METHODS: The MEDLINE, HealthSTAR, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
381
1
21

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 555 publications
(413 citation statements)
references
References 105 publications
(114 reference statements)
10
381
1
21
Order By: Relevance
“…The mean weight loss for the three single-group studies (20,31,24) was 8.2±5 pounds, whereas the three quasi-experimental studies (24,25,28) and four randomized controlled trials (2123,35) showed more modest average weight loss (6.2±.4 pounds and 3.4±2.9 pounds, respectively). The mean for the randomized controlled trials reviewed falls below the mean weight loss reported in meta-analyses of randomized controlled trials of lifestyle interventions tested in the general population, which was eight to 11 pounds (44,45). The difference in weight loss outcomes between the general population and persons with serious mental illness may be due to variability in treatment intensity, worse health status at baseline among persons with serious mental illness, or methodological differences across studies.…”
Section: Discussionmentioning
confidence: 79%
“…The mean weight loss for the three single-group studies (20,31,24) was 8.2±5 pounds, whereas the three quasi-experimental studies (24,25,28) and four randomized controlled trials (2123,35) showed more modest average weight loss (6.2±.4 pounds and 3.4±2.9 pounds, respectively). The mean for the randomized controlled trials reviewed falls below the mean weight loss reported in meta-analyses of randomized controlled trials of lifestyle interventions tested in the general population, which was eight to 11 pounds (44,45). The difference in weight loss outcomes between the general population and persons with serious mental illness may be due to variability in treatment intensity, worse health status at baseline among persons with serious mental illness, or methodological differences across studies.…”
Section: Discussionmentioning
confidence: 79%
“…Despite numerous observed landmarks on clinical existence of the obesity paradox, one must not disregard that lifestyle modifications and obesity treatment must be the mainstay of therapeutic measures in order to improve outcomes from the cardiovascular disease continuum (25)(26)(27)(28). Treatment of obesity is connected with multiple health benefits, particularly the common risk factors as diabetes, chronic renal disease, hypertension and related to the decrease in total or cardiovascular mortality (17,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…In another systematic review of 16 studies that used diet but without pharmacological intervention, and that had >100 subjects in each group and a duration of >1 year, weight loss after 2-3 years was usually <5 kg below baseline (3.5 ± 2.4 kg; range, 0.9-10.0 kg), and after 4-7 years where there were data, it was 3.6 kg ± 2.6 kg below baseline. 7 Portion-controlled diets are one way of achieving a balanced caloric deficit. This can be done most simply by using individually packaged foods.…”
Section: Balanced-deficit Dietsmentioning
confidence: 99%